Perilaku Berjemur pada Kupu-Kupu Junonia atlites dan Junonia hedonia - Yulminarti Yulminarti; Raden Roro Murni Setyowati (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to analyze the effect of wing color on the posture and duration of sunbathing of the butterflies Junonia hedonia and Junonia atlites. The method used in this research is descriptive quantitative with a side method in purposive sampling. Data were collected by following and recording the butterfly sunbathing activity for 120 seconds, measuring air temperature and light intensity. The object of this research is Junonia atlites and J. hedonia. The results showed that J. atlites and J. hedonia demonstrated appressed and/or horizontal postures with the highest frequency (94.44% and 63.33%) in the morning. On the other hand, this frequency decreases in subsequent times. In conclusion, wing color has no effect on the posture displayed and the duration of sunbathing in both species is getting shorter when the air temperature is increasing, but there is no significant effect between the two. The duration of basking is not affected by the color of the wings. Keywords: Butterfly, Sun Behavior, Wing Color